Doped lithium-rich manganese-based positive electrode material and preparation method thereof

By using a multi-element synergistic doping method, a doped lithium-rich manganese-based cathode material was prepared, which solved the problems of irreversible capacity loss and cycle stability during the first charge and discharge process, and improved the electrochemical performance and rate performance of the material.

CN121331815APending Publication Date: 2026-01-13天津常兴新能源科技有限公司

Patent Information

Application Number
CN202511869937.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-12
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

Lithium-rich manganese-based cathode materials suffer from severe irreversible capacity loss during the first charge and discharge process, low initial coulombic efficiency, structural changes during cycling, and poor rate performance, failing to meet the requirements of fast charging and high power output.

Method used

By employing a multi-element synergistic doping method, a doped lithium-rich manganese-based cathode material is prepared through the mixing and solid-state sintering of high-valence transition metals, rare earth elements, alkaline earth elements, and alkali metal elements, thereby improving the overall performance of the material.

Benefits of technology

It significantly improves the material's initial coulombic efficiency and cycle stability, enhances its structural stability and ion transport capacity, reduces interfacial side reactions, and optimizes its electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121331815A_ABST
    Figure CN121331815A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a doped lithium-rich manganese-based positive electrode material and a preparation method thereof, the molecular formula of the doped lithium-rich manganese-based positive electrode material is LiaNibCocMndAWBxCyDzO2, 1.13 < = a < = 1.20, 0.10 < = b, c and d < = 0.80, 0.001 < = w, and x, y and z < = 0.03; wherein A is one or more of high-valence transition metal elements such as W < 6 + >, Mo < 6 + >, Ta < 5 + >, Nb < 5 + > and Ti < 4 + >, B is one or more of rare earth elements such as La < 3 + >, Y < 3 + > and Ce < 4 + >, C is one or more of alkaline earth elements such as Sr < 2 + >, Mg < 2 + > and Ba < 2 + >, and D is one or more of alkaline metal elements such as Li < + >, Na < + > and K < + >. According to the technical scheme, the synergistic effect of multiple elements is achieved, the comprehensive performance such as the first coulombic efficiency and the cycling stability of the lithium-rich manganese-based positive electrode material can be remarkably improved, the preparation method is simple, the lithium-rich manganese-based positive electrode material can be prepared through simple mixing and multi-element synergistic doping solid-phase sintering, the requirement for equipment is low, and the application range is wide. And large-scale popularization of the process is facilitated, and the market competitiveness of the product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of lithium ion batteries, and particularly relates to a doped lithium-rich manganese-based positive electrode material and a preparation method thereof. BACKGROUND

[0002] With the rapid development of electric vehicles, portable electronic devices and large-scale energy storage systems, there is an increasing demand for lithium ion batteries with high energy density, long cycle life and low cost. The positive electrode material is a key component of a lithium ion battery, and its performance directly affects important indicators such as the energy density, cycle life and safety of the battery. Lithium-rich manganese-based positive electrode materials are considered as a potential next-generation lithium ion battery positive electrode material due to their high specific capacity (theoretical specific capacity can reach more than 400 mAh / g), abundant manganese resources and low cost.

[0003] However, lithium-rich manganese-based positive electrode materials face many challenges in practical applications. For example, there is a serious irreversible capacity loss during the first charge and discharge process, and the first coulombic efficiency is low, usually only 70%-80%. During the cycle process, the material is prone to structural phase transition, such as from a layered structure to a spinel phase, resulting in rapid capacity decay and poor cycle stability. In addition, the material has poor rate performance during high-rate charge and discharge, which cannot meet the demand for fast charging and high-power output. To solve these problems, the prior art has adopted various methods to modify lithium-rich manganese-based positive electrode materials. Among them, doping is a common means. Although single-element doping can improve certain properties of the material to some extent, such as stabilizing the structure of the material by doping Y, Sr and other elements, the effect of improving the comprehensive performance of the material is limited. Therefore, it is of great practical significance and urgent need to develop a modification method that can effectively improve the comprehensive performance of lithium-rich manganese-based positive electrode materials. SUMMARY

[0004] In view of the above problems, the present application provides a doped lithium-rich manganese-based positive electrode material and a preparation method thereof, the main purpose of which is to provide an innovative method for modifying the material by multi-element synergistic doping during sintering, aiming to significantly improve the comprehensive performance of lithium-rich manganese-based positive electrode materials such as the first coulombic efficiency and cycle stability, which can be prepared by simple mixing and multi-element synergistic doping solid-phase sintering, with very low requirements for equipment, which is conducive to large-scale promotion of the process and improves the market competitiveness of the product.

[0005] In the first aspect, the present application provides a doped lithium-rich manganese-based positive electrode material, the molecular formula of which is Li a Ni b Co c Mn d A W B x Cy D z O2, wherein, 1.13≤a≤1.20, 0.10≤b, c, d≤0.80, 0.001≤w, x, y, z≤0.03;

[0006] wherein, A is one or several of high-valence transition metal elements W 6+ , Mo 6+ , Ta 5+ , Nb 5+ , Ti 4+ , B is one or several of rare earth elements La 3+ , Y 3+ , Ce 4+ , C is one or several of alkaline earth elements Sr 2+ , Mg 2+ , Ba 2+ , and D is one or several of alkali elements Li + , Na + , K + .

[0007] Optionally, the molar amount of each of the high-valence transition metal element, the rare earth element, the alkaline earth element and the alkali element accounts for 0.1%-3% of the total molar amount of metal elements in the lithium-rich manganese-based precursor.

[0008] In a second aspect, the present application further provides a preparation method of the doped lithium-rich manganese-based positive electrode material, for preparing the doped lithium-rich manganese-based positive electrode material provided in the first aspect, comprising the following steps:

[0009] Step 1, according to the required stoichiometric ratio, weighing the high-valence transition metal element dopant, the rare earth element dopant, the alkaline earth element dopant, the alkali element dopant, the lithium-rich manganese-based precursor and the lithium source, and mixing uniformly;

[0010] Step 2, pre-sintering the mixture to obtain a doped lithium-rich manganese-based precursor, so that the high-valence transition metal element, the rare earth element, the alkaline earth element and the alkali element are preliminarily diffused into the crystal lattice of the lithium-rich manganese-based precursor;

[0011] Step 3, second sintering the doped lithium-rich manganese-based precursor, so that the high-valence transition metal element, the rare earth element, the alkaline earth element and the alkali element are uniformly doped in the bulk phase of the lithium-rich manganese-based material, to obtain the doped lithium-rich manganese-based positive electrode material.

[0012] Optionally, the high-valence transition metal element dopant comprises one or several of molybdenum trioxide, molybdenum trihydroxide, molybdenum oxalate, tungsten trioxide, tungsten trihydroxide, tantalum pentoxide, tantalum hydroxide, tantalum oxalate, niobium pentoxide, niobium hydroxide, niobium oxalate, niobium phosphate, titanium dioxide, titanium hydroxide, and titanium oxalate.

[0013] The rare earth element dopant includes one or more of yttrium oxide, yttrium hydroxide, yttrium oxalate, lanthanum oxide, lanthanum hydroxide, lanthanum oxalate, cerium oxide, cerium hydroxide, and cerium oxalate;

[0014] The alkaline earth element dopant includes one or more of strontium oxide, strontium hydroxide, strontium oxalate, magnesium oxide, magnesium hydroxide, magnesium oxalate, barium oxide, barium hydroxide, and barium oxalate;

[0015] The alkali metal element dopant includes one or more of lithium hydroxide, lithium oxalate, lithium carbonate, sodium carbonate, sodium hydroxide, potassium carbonate, and potassium hydroxide.

[0016] Optionally, the mixing mode in step 1 is high-speed stirring, the rotation speed of high-speed stirring is 300-1000 r / min, and the high-speed stirring time is 30-200 min.

[0017] Optionally, in step 2, the pre-sintering temperature is 400-600°C, and the pre-sintering time is 2-4 h.

[0018] In step 3, the second sintering temperature is 800-1000°C, and the second sintering time is 6-14 h.

[0019] Optionally, the lithium source includes lithium carbonate or lithium hydroxide.

[0020] Optionally, the median particle size D50 of the lithium-rich manganese-based precursor is 10-12 μm.

[0021] Optionally, in step 1, the molar ratio of lithium in the lithium source to metal elements in the lithium-rich manganese-based precursor is (1.13-1.2):1.

[0022] In a third aspect, the present disclosure further provides a lithium ion battery comprising the doped lithium-rich manganese-based positive electrode material provided in the first aspect.

[0023] Compared with the prior art, the technical solution provided by the present application has the following advantages:

[0024] (1) The high-valence transition metal element (such as Mo 6+ ) has a radius close to that of Mn 4+ , can replace part of the Mn sites, and can enhance the Mo-O bond strength (Mo-O bond energy is higher than Mn-O) through high electric price to inhibit the disproportionation reaction of Mn 3+ and the dissolution of Mn; the radius of the rare earth element (such as Y 3+ ) is greatly different from that of the high-valence element (for example, Mn 4+ ), and it is easier to occupy the lattice gap or surface site, and can fix the oxygen skeleton through strong Y-O bond to inhibit the release of oxygen and the disintegration of the layered structure; the radius of the alkaline earth element (such as Sr2+ ) Large radius, can widen the interlayer spacing, and the +2 charge can neutralize the high valence state of some transition metals (such as Mn 4+ ), relieve lattice stress; and rare earth elements such as Y 3+ cooperate, Y 3+ stabilize the internal structure; alkaline earth elements (such as Sr 2+ ) can optimize the interlayer channel and reduce volume expansion; alkali elements (such as Na + ) and Li + have similar radii and can partially replace Li sites, and the weak mobility of Na + can inhibit Li + / Ni 2+ mixing, and the introduction of alkali elements such as Na + can adjust the electronic state of the crystal and reduce the energy barrier of structural phase transition.

[0025] (2) Multi-element synergistic doping significantly enhances structural stability: the synergistic effect of elements of different sizes and valences can more evenly occupy lattice sites, inhibiting the transformation of the layered structure to spinel phase. For example, the combination of high-valence transition metal elements and rare earth elements can both stabilize the oxygen framework through strong chemical bonds and inhibit lattice distortion through differences in ionic radii, and their structural stability effect is much better than that of single-element doping.

[0026] (3) Multi-element synergistic doping comprehensively improves ion transport capacity: the introduction of alkaline earth elements or alkali elements can expand the interlayer spacing to provide a channel for lithium ion migration, and high-valence transition metal elements can reduce charge transfer resistance.

[0027] (4) Multi-element synergistic doping effectively inhibits interface side reactions: the enrichment effect of rare earth elements can form a stable protective layer on the surface of the material, and in combination with the regulating effect of alkali elements on the electrolyte, it can simultaneously reduce transition metal dissolution and electrolyte decomposition, and reduce interface impedance.

[0028] (5) Multi-element synergistic doping balances and optimizes the electrochemical performance: multi-element synergistic doping can achieve "multiple gains" through functional distribution, enabling both the initial coulombic efficiency and the cycle life to reach a high level.

[0029] In addition, the preparation method of the doped lithium-rich manganese-based positive electrode material provided by the present application is simple, and the material can be prepared through simple mixing and multi-element synergistic doping solid-phase sintering, which has low requirements for equipment and is conducive to large-scale promotion of the process, thereby improving the market competitiveness of the product. BRIEF DESCRIPTION OF DRAWINGS

[0030] The accompanying drawings, which are incorporated into and form part of the specification, illustrate embodiments consistent with the present disclosure and, together with the specification, serve to explain the principles of the present disclosure.

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure or the prior art, the drawings needed to be used in the embodiments or prior art description will be briefly introduced as follows. Obviously, those skilled in the art can obtain other drawings according to these drawings without any creative effort.

[0032] Figure 1 SEM image of the doped lithium-rich manganese-based positive electrode material provided for Example 1;

[0033] Figure 2 XRD image of the doped lithium-rich manganese-based positive electrode material provided for Example 1;

[0034] Figure 3 SEM image of the doped lithium-rich manganese-based positive electrode material provided for Example 2;

[0035] Figure 4 XRD image of the doped lithium-rich manganese-based positive electrode material provided for Example 2;

[0036] Figure 5 SEM image of the lithium-rich manganese-based positive electrode material provided for Comparative Example 1;

[0037] Figure 6 XRD image of the lithium-rich manganese-based positive electrode material provided for Comparative Example 1;

[0038] Figure 7 SEM image of the lithium-rich manganese-based positive electrode material provided for Comparative Example 2;

[0039] Figure 8 XRD image of the lithium-rich manganese-based positive electrode material provided for Comparative Example 2;

[0040] Figure 9 SEM image of the lithium-rich manganese-based positive electrode material provided for Comparative Example 3;

[0041] Figure 10 XRD image of the lithium-rich manganese-based positive electrode material provided for Comparative Example 3;

[0042] Figure 11 SEM image of the lithium-rich manganese-based positive electrode material provided for Comparative Example 4;

[0043] Figure 12 XRD image of the lithium-rich manganese-based positive electrode material provided for Comparative Example 4;

[0044] Figure 13 Charge-discharge performance graph of the doped lithium-rich manganese-based positive electrode material provided for Example 1;

[0045] Figure 14 Charge-discharge performance graph of the doped lithium-rich manganese-based positive electrode material provided for Example 2;

[0046] Figure 15 Charge-discharge performance chart of the lithium-rich manganese-based positive electrode material provided for Comparative Example 1;

[0047] Figure 16 Charge-discharge performance chart of the lithium-rich manganese-based positive electrode material provided for Comparative Example 2;

[0048] Figure 17 Charge-discharge performance chart of the lithium-rich manganese-based positive electrode material provided for Comparative Example 3;

[0049] Figure 18 Charge-discharge performance chart of the lithium-rich manganese-based positive electrode material provided for Comparative Example 4;

[0050] Figure 19 Cycle performance chart of the doped lithium-rich manganese-based positive electrode material provided for Examples 1-2 and the lithium-rich manganese-based positive electrode material provided for Comparative Examples 1-4. DETAILED DESCRIPTION

[0051] In order to enable a more complete understanding of the above-mentioned objects, features and advantages of the present disclosure, the schemes of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.

[0052] In the following description, a large number of specific details are set forth in order to facilitate a thorough understanding of the present disclosure, but the present disclosure can also be implemented in other manners different from those described herein; obviously, the embodiments described in the specification are only a part of the embodiments of the present disclosure, and not all the embodiments.

[0053] In order to better understand the present application, the following provides examples and comparative examples of the preparation method of the doped lithium-rich manganese-based positive electrode material.

[0054] Example 1

[0055] According to the stoichiometric molar ratio, 2.32 g of molybdenum trioxide, 5.83 g of yttrium oxalate, 1.11 g of strontium oxide, 0.43 g of sodium hydroxide, 100 g of lithium-rich manganese-based precursor Ni 0.13 Co 0.13 Mn 0.54 (CO3) 0.8 , 47 g of lithium carbonate were weighed, and each substance was mixed by high-speed stirring at a rotation speed of 1000 r / min for 60 min. The mixed material was transferred to a muffle furnace, pre-sintered at 500℃ for 3 h to preliminarily diffuse the doping elements into the crystal lattice of the lithium-rich manganese-based precursor, and then sintered at 800℃ for 10 h to complete the sintering of the doped lithium-rich manganese-based positive electrode material, thereby obtaining Li 1.15 Ni 0.13 Co 0.13 Mn0.54 Mo 0.015 Y 0.02 Sr 0.01 Na 0.01 O2.

[0056] Figure 1 The SEM image of the doped lithium-rich manganese-based positive electrode material provided for Example 1 shows the morphology of Example 1 at unit sizes of 100 nm and 1 μm, as shown in Figure 1 The doped lithium-rich manganese-based positive electrode material after sintering has uniform secondary particle size, large pore size, and good density, as shown in Figure 2 The XRD image of the doped lithium-rich manganese-based positive electrode material provided for Example 1 is shown in Figure 2 The abscissa in the XRD image is the diffraction angle 2theta (θ), i.e., twice the Bragg angle, and the ordinate is the diffraction intensity (Intensity) in a.u. The abscissa and ordinate of the XRD images of subsequent Example 2 and Comparative Examples 1-4 can be understood in this way, and will not be described again. As shown in Figure 2 The successfully synthesized lithium-rich manganese-based positive electrode material of the layered structure belongs to the hexagonal system, has a narrow half-peak width, and high peak intensity, indicating that the material has good crystallinity.

[0057] Example 2

[0058] The specific steps and methods are the same as those of Example 1, except that pre-sintering is first performed at 500°C for 3 h to preliminarily diffuse the doping elements into the crystal lattice of the lithium-rich manganese-based precursor, and then high-temperature sintering is performed at 850°C for 10 h.

[0059] Figure 3 The SEM image of the doped lithium-rich manganese-based positive electrode material provided for Example 2 shows the morphology of Example 2 at unit sizes of 100 nm and 1 μm, as shown in Figure 3 The positive electrode material after sintering has uniform secondary particle size, small pore size, and good density, as shown in Figure 4 The XRD image of the doped lithium-rich manganese-based positive electrode material provided for Example 2 is shown in Figure 4 The successfully synthesized lithium-rich manganese-based positive electrode material of the layered structure belongs to the hexagonal system, has a narrow half-peak width, and high peak intensity, indicating that the material has good crystallinity.

[0060] Comparative Example 1

[0061] The specific steps and methods are the same as those of Example 1, except that no molybdenum trioxide, yttrium oxalate, strontium oxide, and sodium hydroxide are added.

[0062] Figure 5 The SEM image of the lithium-rich manganese-based positive electrode material provided for Comparative Example 1 shows the morphology of Comparative Example 1 at unit sizes of 100 nm and 1 μm, as shown inFigure 5 As shown in the SEM image, the sintered positive electrode material has uniform secondary particle size, small secondary particle size, small pore size, and good density. Figure 6 The XRD image of the lithium-rich manganese-based positive electrode material provided for Comparative Example 1 is shown in FIG. 6. Figure 6 As shown in the XRD image, the successfully synthesized lithium-rich manganese-based positive electrode material has a hexagonal structure, a narrow half-peak width, and high peak intensity.

[0063] Comparative Example 2

[0064] The specific steps and methods are the same as those of Example 1, except that yttrium oxalate, strontium oxide, and sodium hydroxide are not added. Figure 7 The SEM image of the lithium-rich manganese-based positive electrode material provided for Comparative Example 2 is shown in FIG. 8. Figure 7 As shown in the SEM image, the sintered positive electrode material has uniform secondary particle size, small secondary particle size, large pore size, and poor density. Figure 8 The XRD image of the lithium-rich manganese-based positive electrode material provided for Comparative Example 2 is shown in FIG. 9. Figure 8 As shown in the XRD image, the successfully synthesized lithium-rich manganese-based positive electrode material has a hexagonal structure, a narrow half-peak width, and high peak intensity.

[0065] Comparative Example 3

[0066] The specific steps and methods are the same as those of Example 1, except that strontium oxide and sodium hydroxide are not added.

[0067] Figure 9 The SEM image of the lithium-rich manganese-based positive electrode material provided for Comparative Example 3 is shown in FIG. 10. Figure 9 As shown in the SEM image, the sintered positive electrode material has uniform secondary particle size, small secondary particle size, small pore size, and very high density. Figure 10 The XRD image of the lithium-rich manganese-based positive electrode material provided for Comparative Example 3 is shown in FIG. 11. Figure 10 As shown in the XRD image, the successfully synthesized lithium-rich manganese-based positive electrode material has a hexagonal structure, a narrow half-peak width, and high peak intensity.

[0068] Comparative Example 4

[0069] The specific steps and methods are the same as those of Example 1, except that sodium hydroxide is not added.

[0070] Figure 11 The SEM image of the lithium-rich manganese-based positive electrode material provided for Comparative Example 4 is shown in FIG. 12. Figure 11 As shown in the SEM image, the sintered positive electrode material has uniform secondary particle size, small secondary particle size, small pore size, and good density. Figure 12The image shows the XRD pattern of the lithium-rich manganese-based cathode material provided in Comparative Example 4. The successfully synthesized layered lithium-rich manganese-based cathode material belongs to the hexagonal crystal system and has a narrow half-width and high peak intensity.

[0071] The positive electrode materials prepared in Examples 1, 2, 1, 2, 3, and 4 were mixed with a conductive agent (carbon black) and a binder (polyvinylidene fluoride) in a mass ratio of 80:10:10 to prepare a positive electrode slurry, which was then coated onto aluminum foil to form a positive electrode sheet. After drying, the slurry was assembled with a lithium metal negative electrode sheet, a polypropylene microporous membrane separator, and an electrolyte in a glove box to form a standard 2032 button battery. After aging for 12 hours, charge-discharge tests were conducted at a voltage range of 2.0V-4.8V and 2.0V-4.6V, at a test temperature of 25℃. The electrochemical performance test results of the doped lithium-rich manganese-based positive electrode material are listed in Table 1.

[0072] Figures 13-18 In the provided charge / discharge performance graph, the horizontal axis represents specific capacity, with units of mAh g. -1 The vertical axis represents voltage, with the unit being V. Figure 19 The graphs show the cycle performance of the doped lithium-rich manganese-based cathode materials provided in Examples 1-2 and the lithium-rich manganese-based cathode materials provided in Comparative Examples 1-4. The horizontal axis represents the number of cycles, and the vertical axis represents the specific capacity. The units are mAh g. -1 .

[0073] Table 1 Electrochemical performance test results of doped lithium-rich manganese-based materials

[0074]

[0075] Combined with Table 1, Figures 13-19 As can be seen from the electrochemical performance test, the doped lithium-rich manganese-based cathode material prepared by this invention can achieve a discharge specific capacity of 288 mAh g at a 0.1C rate within a voltage range of 2.0V-4.8V. -1 Above, within a voltage range of 2.0V-4.6V, the discharge specific capacity at a 0.1C rate can reach 260 mAh g. -1 The discharge specific capacity at 1C rate can reach 210 mAh g. -1The above results show that the capacity retention rate after 100 cycles at 1C rate can reach over 87%, and the average voltage decay after 100 discharge cycles at 1C rate can be as low as 0.58 mV. In contrast, Comparative Examples 1-4 exhibit poorer electrochemical performance. This indicates that doping lithium-rich manganese-based cathode materials with high-valence transition metals, rare earth elements, alkaline earth elements, and alkali metals can significantly improve the electrochemical performance of these materials, effectively enhancing their structural stability and conductivity, thereby improving the battery's cycle life and overall performance.

[0076] As can be seen from Example 2 and Comparative Examples 1-4, the synergistic doping of four elements—high-valence transition metal elements, rare earth elements, alkaline earth elements, and alkali metal elements—can simultaneously improve the overall electrochemical performance of the battery, including discharge specific capacity, initial efficiency, and cycle life.

[0077] As can be seen from Examples 2 and 1, an appropriate sintering temperature can better promote the diffusion of dopants into the lattice of lithium-rich manganese-based precursors, thereby improving the overall performance of the battery, such as discharge specific capacity, first efficiency, and cycle life.

[0078] Although the present invention has been described above, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many modifications under the guidance of the present invention without departing from the spirit of the present invention, and these modifications are all within the protection scope of the present invention.

Claims

1. A doped lithium-rich manganese-based cathode material, characterized in that, The molecular formula of the doped lithium-rich manganese-based cathode material is Li a Ni b Co c Mn d A W B x C y D z O2, 1.13≤a≤1.20, 0.10≤b, c, d≤0.80, 0.001≤w, x, y, z≤0.03; Where A is the high-valence transition metal element W 6+ Mo 6+ Ta 5+ 、Nb 5+ Ti 4+ One or more of them, where B is the rare earth element La. 3 + Y 3+ Ce 4+ One or more of the elements, where C is an alkaline earth element and Sr is a saturated ore. 2+ Mg 2+ Ba 2+ One or more of them, where D is an alkali metal element Li. + Na + K + One or more of them.

2. The doped lithium-rich manganese-based cathode material according to claim 1, characterized in that, The molar amounts of the high-valence transition metal element, the rare earth element, the alkaline earth element, and the alkali metal element each account for 0.1%-3% of the total molar amounts of metal elements in the lithium-rich manganese-based precursor.

3. A method for preparing a doped lithium-rich manganese-based cathode material, characterized in that, The preparation of the doped lithium-rich manganese-based cathode material as described in any one of claims 1-2 includes the following steps: Step 1: Weigh out the high-valence transition metal element dopant, rare earth element dopant, alkaline earth element dopant, alkali metal element dopant, lithium-rich manganese-based precursor and lithium source according to the required stoichiometric ratio, and mix them evenly. Step 2: Pre-sinter the mixture to obtain a doped lithium-rich manganese-based precursor, so that high-valence transition metal elements, rare earth elements, alkaline earth elements and alkali metal elements are initially diffused into the lattice of the lithium-rich manganese-based precursor. Step 3: The doped lithium-rich manganese-based precursor is sintered a second time to uniformly dope high-valence transition metal elements, rare earth elements, alkaline earth elements and alkali metal elements in the bulk phase of the lithium-rich manganese-based material, thereby obtaining the doped lithium-rich manganese-based cathode material.

4. The method for preparing the doped lithium-rich manganese-based cathode material according to claim 3, characterized in that, The high-valence transition metal element dopants include one or more of the following: molybdenum trioxide, molybdenum trihydride, molybdenum oxalate, tungsten trioxide, tungsten trihydride, tantalum pentoxide, tantalum hydroxide, tantalum oxalate, niobium pentoxide, niobium hydroxide, niobium oxalate, niobium phosphate, titanium dioxide, titanium hydroxide, and titanium oxalate. The rare earth element dopants include one or more of yttrium oxide, yttrium hydroxide, yttrium oxalate, lanthanum oxide, lanthanum hydroxide, lanthanum oxalate, cerium oxide, cerium hydroxide, and cerium oxalate; The alkaline earth element dopant includes one or more of strontium oxide, strontium hydroxide, strontium oxalate, magnesium oxide, magnesium hydroxide, magnesium oxalate, barium oxide, barium hydroxide, and barium oxalate. The alkali metal element dopant includes one or more of lithium hydroxide, lithium oxalate, lithium carbonate, sodium carbonate, sodium hydroxide, potassium carbonate, and potassium hydroxide.

5. The method for preparing the doped lithium-rich manganese-based cathode material according to claim 3, characterized in that, The mixing method in step 1 is high-speed stirring, with a stirring speed of 300-1000 r / min and a stirring time of 30-200 min.

6. The method for preparing the doped lithium-rich manganese-based cathode material according to claim 3, characterized in that, In step 2, the pre-sintering temperature is 400-600℃ and the pre-sintering time is 2-4h; In step 3, the temperature of the second sintering is 800-1000℃, and the time of the second sintering is 6-14h.

7. The method for preparing the doped lithium-rich manganese-based cathode material according to claim 3, characterized in that, The lithium source includes one or more of lithium carbonate and lithium hydroxide.

8. The method for preparing the doped lithium-rich manganese-based cathode material according to claim 3, characterized in that, The median particle size D50 of the lithium-rich manganese-based precursor is 10-12 μm.

9. The method for preparing the doped lithium-rich manganese-based cathode material according to claim 3, characterized in that, In step 1, the molar ratio of lithium in the lithium source to metal in the lithium-rich manganese-based precursor is (1.13 - 1.2):

1.

10. A lithium-ion battery, characterized in that, Including the doped lithium-rich manganese-based cathode material as described in any one of claims 1-2.

Citation Information

Patent Citations

  • Molybdenum-doped lithium-rich manganese-based cathode material and preparation method thereof

    CN107768664A

  • Rare earth element modified lithium ion battery positive electrode material and preparation method and application thereof

    CN110911687A

  • Doped lithium-rich manganese oxide positive electrode material and preparation method and application thereof

    CN119361676A

  • Lithium-rich manganese-based material for all-solid-state battery as well as preparation method and application of lithium-rich manganese-based material

    CN119706967A

  • Doped Lithium-Rich Layered Composite Cathode Materials

    US20150270545A1

Cited By

  • Cation-doped lithium-rich manganese-based positive electrode material, preparation method thereof and battery

    CN122511819A